Bad Touches, Getting Away, and Never Keeping Secrets: Assessing Student Knowledge Retention of the "Red Flag Green Flag People" Program. (October 2015) - Wood, McKenzie; Archbold, Carol A.
School-based prevention programs that target sexual abuse are commonplace in many elementary schools across the United States. This study examines the efficacy of the "Red Flag Green Flag People" program presented to elementary school children in two school districts in the Midwest. A brief, 11-question survey is given to students to assess knowledge retention of the curriculum from this sexual abuse prevention program. The results of this study indicate that students are retaining information taught in the Red Flag Green Flag People program for up to 2 years after the program was administered.